Professional Development Coaching for Health Professions Graduate Faculty: A Pilot Implementation. Issue 4 (27th December 2022) - Pearce, Michelle J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Organizations have offered executive coaching to their senior leaders for several decades and report improvement in performance, leadership, self-efficacy, and goal attainment. Despite this success, little research exists on coaching programs for faculty who may also benefit from this resource. We sought to develop, implement, and evaluate a professional development coaching program for diverse graduate faculty at a health professions university. Methods: We implemented a professional development coaching program to provide one-on-one support for interested faculty. Faculty were offered four 1-hour or eight half-hour sessions each academic semester by eight trained volunteer coaches unaffiliated with the university. We had 67 faculty members participate across the academic year. They were asked to complete a brief impact survey at the end of each semester. Results: The coaches provided 378 sessions, totaling 281 hours of coaching. Survey results revealed that coaching was effective in helping faculty achieve their professional goals and empowered them for future professional success. Faculty were highly satisfied with the program. Discussion: There is early evidence that professional development coaching can help faculty reach their professional goals and add value to an institution. The program may be a helpful model for developing and implementing coaching programs on other campuses.